Diesel engine waste heat recovery turbine design: geometric and materials effects on ORC turbines - Dragos, Alexandru Vasile; Pesyridis, Apostolos; Alshammari, Fuhaid; Sphicas, Panos; Kourmpetis, Miltiadis (Frontiers in Mechanical Engineering, 2023)
The significance of this work is the demonstration that an ORC (Organic Rankine Cycle) system can be successfully implemented on heavy-duty vehicles and contribute to fuel consumption (and emissions) reduction. Additionally, this paper focuses on providing due consideration to the materials aspects of the most critical component of the ORC system, namely, the turbine—expander. The expander of an ORC system optimized off an experimental prototype coupled to a 7 L diesel engine and optimized from the point of view of the rotor geometry, materials and clearances to be applicable to the specific experimental setup. The optimum clearance between the rotor blades and shroud, in terms of performance and economical aspects, was calculated at 0.4 mm. Based on the initial geometry of the ORC turbine, for this particular application and optimising for performance, refrigerant R134a was found to be the best choice. Then the rotor geometry was optimized using ANSYS simulation. The maximum performance obtained by the expander to achieve 72.95% total to static isentropic efficiency. It was calculated on GT-Power that the optimized ORC system, implemented on a heavy-duty vehicle, can reduce fuel consumption by up to 17%.